2017
DOI: 10.1002/lary.26816
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with patient no‐show rates in an academic otolaryngology practice

Abstract: 4. Laryngoscope, 128:626-631, 2018.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
77
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 56 publications
(92 citation statements)
references
References 24 publications
11
77
4
Order By: Relevance
“…9 Our group recently completed a study of nearly 23 000 patient visits and found several factors related to noshow rates in the academic otolaryngology setting as listed above. 2 What factors to target to decrease no-show rates is clearly a very complex question. The present review of data was not designed to answer this question but rather to report baseline data in the hospital-employed, nonacademic physician practice.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…9 Our group recently completed a study of nearly 23 000 patient visits and found several factors related to noshow rates in the academic otolaryngology setting as listed above. 2 What factors to target to decrease no-show rates is clearly a very complex question. The present review of data was not designed to answer this question but rather to report baseline data in the hospital-employed, nonacademic physician practice.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, we found a no-show rate of 8.4%, which is much lower than other reported no-show rates within academic otolaryngology practices. 1,2 This may be due to the patient population or geographical practice setting. However, this lower rate may be secondary to the preappointment reminders utilized in this practice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 Consequences of appointment nonadherence include lost revenue and worsened patient outcomes. Several studies have identified factors associated with increased no-show rates, [2][3][4] including prior history of missed appointments, new patient visits, time between scheduling and actual appointment, and insurance provider. 3,4 Most studies focusing on this topic have been performed in nonacademic primary care clinics, and little data exist on factors specific to pediatric dermatology.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have identified factors associated with increased no-show rates, [2][3][4] including prior history of missed appointments, new patient visits, time between scheduling and actual appointment, and insurance provider. 3,4 Most studies focusing on this topic have been performed in nonacademic primary care clinics, and little data exist on factors specific to pediatric dermatology. 4,5 Due to the paucity of board-certified pediatric dermatologists, it is important to reduce appointment nonadherence in order to optimize the number of patients with access to pediatric dermatology services.…”
Section: Introductionmentioning
confidence: 99%